Regional Banking Instability and FOMC Voting - Stefan Eichler; Tom Lähner; Felix Noth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
This study analyzes if regionally affiliated Federal Open Market Committee (FOMC) members take their districts' regional banking sector instability into account when they vote. Considering the period from 1978 to 2010, we find that a deterioration in a district's bank health increases the probability that this district's representative in the FOMC votes to ease interest rates. According to member-specific characteristics, the effect of regional banking sector instability on FOMC voting behavior is most pronounced for Bank presidents (as opposed to governors) and FOMC members who have career backgrounds in the financial industry or who represent a district with a large banking sector.
urn:nbn:de:gbv:3:2-54629
Keywords: E43; E52; E58; G21; 330; FOMC voting; regional banking sector instability; lobbying